Origin and Evolution of Antibiotic Resistance: The Common Mechanisms of Emergence and Spread in Water Bodies - Lupo, Agnese; Coyne, Sebastien; Berendonk, Thomas U. (Frontiers in Microbiology, 2012)
The environment, and especially fresh water, constitutes a reactor where the evolution and the rise of new resistances occur. In rivers or streams, bacteria from different sources such as urban, industrial and agricultural waste, probably selected by intensive antibiotic usage, are collected and mixed with environmental species. This may cause two effects on the development of antibiotic resistances: First, the contamination of water by antibiotics or other pollutants lead to the rise of resistance due to selection processes. For instance, of strains over-expressing broad range defensive mechanisms, such as efflux pumps. Second, since environmental species are provided with intrinsic antibiotic resistance mechanisms, the mixture with allochthonous species is likely to cause genetic exchange. In this context, the role of phages and integrons for the spread of resistance mechanisms appears significant. Allochthonous species could acquire new resistances from environmental donors and introduce the newly acquired resistance mechanisms into the clinics. This is illustrated by clinically relevant resistance mechanisms, such as the fluoroquinolones resistance genes qnr. Freshwater appears to play an important role in the emergence and in the spread of antibiotic resistances, highlighting the necessity for strategies of water quality improvement. Moreover, further knowledge is needed to better understand the role of the environment as reservoir of antibiotic resistances and to assess the risk of spread of antibiotic resistances via water bodies.